Influence of Connection Placement to the Behavior of Precast Concrete Exterior Beam-Column Joint - Tjahjono, Elly; Purnomo, Heru (UI Scholars Hub, 2004)
Influence of Connection Placement to the Behavior of Precast Concrete Exterior Beam-Column Joint. This paper presents an experimental study on the influence of connection placement to the behaviour of exterior beamcolumn joint of precast concrete structure under semi cyclic loading. Four half-scale beam-column specimens were investigated. Three beam-columns were jointed through connection that are placed in beam-column joint region and the forth is connected at the plastic hinge potensial region of the beam. Crack patterns, strength, stiffness and ductility of the test specimens have been evaluated. The test result indicated that all beam-column specimens show good ductility behavior.